Case series of seven cases of urticaria, angioedema, and anaphylaxis (LTP syndrome) due to foods (nuts, lentils, and citrus foods) related to tree pollen (Prosopis juliflora and Holoptelea integrifolia) sensitization - Kathuria, P C; Rai, Manisha (Indian Journal of Case Reports, 2021)
Lipid transfer protein syndrome (LTPS) results from a primary sensitization to LTP belonging to the PR-14 family of pathogenesis-related PR-proteins which are plant food allergens, stable against heat and digestive enzymes, and can induce systemic reactions of urticaria, angioedema, and anaphylaxis. Here, we report a case series of seven patients with nsLTP syndrome. Our six cases of LTPS were significantly sensitized to Prosopis juliflora and Holoptelea integrifolia and one case was sensitized to H. integrifolia only. In our seven cases, we hypothesized that symptoms of hypersensitivity reaction to foods were due to cross-reactivity by IgE reactive protein of ns-LTP as a major allergenic protein in foods.